Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1364/oe.486393
|View full text |Cite
|
Sign up to set email alerts
|

Optical power degradation mechanisms in 271 nm AlGaN-based deep ultraviolet light-emitting diodes

Abstract: The degradation of AlGaN-based UVC LEDs under constant temperature and constant current stress for up to 500 hrs was analyzed in this work. During each degradation stage, the two-dimensional (2D) thermal distributions, I-V curves, optical powers, combining with focused ion beam and scanning electron microscope (FIB/SEM), were thoroughly tested and analyzed the properties and failure mechanisms of UVC LEDs. The results show that: 1) the opto-electrical characteristics measured before/during stress indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…During the 1000 h aging test, the LOP of UVC LEDs packaged with the 3D PhC reflector and Au plating decreased by 7% and 8%, respectively, as shown in Figure 5 . Various optical power degradation mechanisms have been observed in UVC LEDs at different stages of degradation, including hillock-related and stress-induced defects [ 24 , 25 ]. The results of the 1000 h aging test indicated that UVC LEDs containing 3D PhC samples were nearly consistent with commercial UVC LEDs, and the 3D PhCs deposited on the UVC LED lead frame remained undamaged, demonstrating excellent reliability.…”
Section: Resultsmentioning
confidence: 99%
“…During the 1000 h aging test, the LOP of UVC LEDs packaged with the 3D PhC reflector and Au plating decreased by 7% and 8%, respectively, as shown in Figure 5 . Various optical power degradation mechanisms have been observed in UVC LEDs at different stages of degradation, including hillock-related and stress-induced defects [ 24 , 25 ]. The results of the 1000 h aging test indicated that UVC LEDs containing 3D PhC samples were nearly consistent with commercial UVC LEDs, and the 3D PhCs deposited on the UVC LED lead frame remained undamaged, demonstrating excellent reliability.…”
Section: Resultsmentioning
confidence: 99%
“…Still these interfaces include an intermediate layer of oxidized III-V or SiC, which might be useful to include in theoretical models to predict the properties of these interfaces. Recent studies have presented energetically favored structures for oxidized GaAs (100) and InP(100) surfaces [216,233], which provide a realistic platform to simulate the interface properties and their modifications.…”
Section: Which Interface Defects Do Cause Extra Electron Levels In Th...mentioning
confidence: 99%
“…The third critical factor is durability of the Ohmic contacts. For example, degradation of the Ohmic contact of p-GaN decreases operation time of ultraviolet LED [100].…”
Section: Trade-off Between Ohmic and Recombination Losses At Metal-se...mentioning
confidence: 99%
See 1 more Smart Citation
“…The first mechanism is associated with the complete lack of emission of optical radiation, while the second is associated with its successive loss and from the operational point of view is a significant problem because, despite the actual operation of the system, it leads to a deterioration in the effectiveness of the disinfection process [22]. The gradual degradation of the OP of LED depends on the operating temperature and current density [22,[28][29][30][31][32] and is the fastest during the first 10-200 h of operation, then the process slows down [19,21,[33][34][35][36][37]. According to [22,38], the UVC LED's lifetime is inversely proportional to the third power of the stress current density.…”
Section: Introductionmentioning
confidence: 99%